The protective effect of resveratrol against risperidone-induced liver damage through an action on FAS gene expression - Azirak, Sebile; Bilgic, Sedat; Korkmaz, Deniz Tastemir; Guvenc, Ayse N.; Kocaman, Nevin; Ozer, Mehmet K. (General Physiol and Biophysics, 2019)
The purpose of the study is to examine the protective effect of resveratrol on the fatty acid synthase gene expression against the side-effects of risperidone in an experimental model in rat liver. In this study, thirty-five female Spraque-Dawley rats were divided into five groups (n = 7): Control, RIS (2 mg/kg risperidone daily), RSV1 (2 mg/kg risperidone + 20 mg/kg resveratrol), RSV2 (2 mg/kg risperidone + 40 mg/kg resveratrol), and RSV3 group (2 mg/kg risperidone + 80 mg/kg resveratrol). On treatment day 15, liver tissue was taken for analysis. The resveratrol treatment significantly reduced weight gain as opposed to the risperidone administration. Moreover, the fatty acid synthase gene expression level increased significantly in RSV1 group (p = 0.011). In addition, resveratrol enhanced the total antioxidant status, high-density lipoprotein cholesterol levels and decreased alanine aminotransferase, aspartate aminotransferase, total cholesterol, gamma glutamyl transpeptidase, low density lipoprotein cholesterol, oxidative stress index, triglycerides, and total oxidant status levels significantly (p < 0.05). In conclusion, this study revealed that treatment with resveratrol might protect liver tissue against the side-effects of risperidone over fatty acid synthase gene expression. Resveratrol could be an effective course of therapy for enhancing therapeutic efficacy.
Keywords: Risperidone; Resveratrol; Fatty acid synthase; Liver; Apoptosis